2007
DOI: 10.1007/s10709-007-9197-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of seed flow on the pattern and dynamics of pearl millet (Pennisetum glaucum [L.] R. Br.) genetic diversity assessed by AFLP markers: a study in south-western Niger

Abstract: We studied the regional genetic diversity and seed exchange dynamics of pearl millet landraces in south-western Niger. The genetic study was based on AFLP markers. We found significant genetic differentiation between landraces in different geographical areas of south-western Niger. However, the degree of differentiation was low insofar as only 1.9% of the total molecular diversity was due to regional differentiation, suggesting a relatively high gene flow. Anthropologic studies on farming practices have sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…This was especially observed in the western side of the lake and when comparing landrace populations sampled in the same ethno-linguistic group. This result is fully in agreement with those of Busso et al (2000) in North-eastern Nigeria, and of Allinne et al (2008) in the Zarma-Songhay area. Farming practices have been invoked to explain this pattern.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was especially observed in the western side of the lake and when comparing landrace populations sampled in the same ethno-linguistic group. This result is fully in agreement with those of Busso et al (2000) in North-eastern Nigeria, and of Allinne et al (2008) in the Zarma-Songhay area. Farming practices have been invoked to explain this pattern.…”
Section: Discussionsupporting
confidence: 93%
“…Seeds of non-local landraces acquired from outside sources (markets or NGOs) are mainly consumed, being sown only infrequently (Robert et al , 2005). Allinne et al (2008) have confirmed this preference, showing that seeds, imported for sowing by farmers in two villages of the Zarma-Songhay area in Niger, were genetically much more similar to landraces grown in the same region than to landraces from neighbouring countries. The mechanisms responsible for the relative isolation between pearl millet genetic pools is likely effective nowadays since its fingerprint is still detectable.…”
Section: Discussionmentioning
confidence: 65%
“…Molecular methods, which can now provide significant additional insights into the extent and distribution of diversity and on the ways in which it is correlated with important social, environmental, and management variables have yet to be undertaken on the scale needed except perhaps for sorghum and pearl millet in Africa (e.g. Barnard et al, 2008;Bezancon et al, 2009;Busso et al, 2000;Sagnard et al, 2008;Allinne et al, 2008). With the rapid improvements in methods over the last decades this is now possible on the required scale.…”
Section: Discussionmentioning
confidence: 99%
“…Flowering time in pearl millet is derived from a common domestication event and a strong gene flow between early- and late-flowering landraces is observed (Dussert et al, 2015). The level of gene flow would depend on cycle overlapping, agricultural practices and spatial distribution (Mariac et al, 2006b; Allinne et al, 2007; Lakis et al, 2012). …”
Section: Introductionmentioning
confidence: 99%